Assessing the Efficiency of the Learners Information System in a Rural Philippine National High School - Bete, James Edward; Collera, Angelie (Journal of Interdisciplinary Perspectives, 2025)
The Learners Information System (LIS) was introduced by the Department of Education (DepEd) in the Philippines to streamline administrative processes and enhance educational governance. However, its effectiveness in rural settings remains underexplored. This study evaluates the implementation of LIS in a rural Philippine high school using the E-Government and Digital Inclusion frameworks. A mixed-methods explanatory sequential design was employed, combining surveys and focus group discussions with 69 participants, including teachers, LIS coordinators, and the school principal. Findings reveal that LIS improves record-keeping and reduces administrative workload, but faces significant challenges, including inadequate IT infrastructure, technical failures, high maintenance costs, and limited inclusivity. These barriers hinder its potential to support Sustainable Development Goal 4 (SDG 4) and DepEd’s digital transformation goals. The study recommends targeted investments in IT infrastructure, offline functionalities, stakeholder training, and accessibility features to enhance the efficiency and inclusivity of LIS. Addressing these issues is critical for ensuring equitable digital transformation in rural education.